2019
DOI: 10.3390/biology8040091
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lactic Acid Bacteria (LAB) Antagonizing Vibrio parahaemolyticus: The Pathogen of Acute Hepatopancreatic Necrosis Disease (AHPND) in Whiteleg Shrimp (Penaeus vannamei)

Abstract: Acute hepatopancreatic necrosis disease (AHPND) has recently emerged as a serious disease of cultured shrimp. A total of 19 lactic acid bacteria (LAB) strains isolated from shrimp samples were characterized based on morphological characteristics, biochemical tests, sequencing analysis, and their ability to antagonize Vibrio parahaemolyticus, which causes AHPND in whiteleg shrimp. Results from the agar well diffusion method indicated that 3 out of 19 isolated LAB strains showed the highest antagonizing ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The results showed that 3 among 19 isolated LAB strains have the highest antagonizing ability against AHPND V. parahaemolyticus strain in vitro, generating inhibition zones ranging from 18 to 20 mm in diameter. In addition, the shrimps fed with LAB supplemented diets displayed significantly higher survival (approximately 80%) upon AHPND V. parahaemolyticus challenge [ 102 ]. Recently, Wang et al (2020) demonstrated that the natural product amicoumacins A purified from the cell-free supernatant of Bacillus subtilis BSXE-1601 strain harboured acillibactin, fengycin, surfactin, bacilysin and subtilosin A, which are responsible for both in vitro and in vivo anti- Vibrio activity against AHPND-causing V. parahaemolyticus strain in L. vannamei [ 103 ].…”
Section: Control and Management Of Acute Hepatopancreatic Necrosis Disease (Ahpnd)—current Statusmentioning
confidence: 99%
“…The results showed that 3 among 19 isolated LAB strains have the highest antagonizing ability against AHPND V. parahaemolyticus strain in vitro, generating inhibition zones ranging from 18 to 20 mm in diameter. In addition, the shrimps fed with LAB supplemented diets displayed significantly higher survival (approximately 80%) upon AHPND V. parahaemolyticus challenge [ 102 ]. Recently, Wang et al (2020) demonstrated that the natural product amicoumacins A purified from the cell-free supernatant of Bacillus subtilis BSXE-1601 strain harboured acillibactin, fengycin, surfactin, bacilysin and subtilosin A, which are responsible for both in vitro and in vivo anti- Vibrio activity against AHPND-causing V. parahaemolyticus strain in L. vannamei [ 103 ].…”
Section: Control and Management Of Acute Hepatopancreatic Necrosis Disease (Ahpnd)—current Statusmentioning
confidence: 99%
“…The application of biological methods is effective to limit drug resistance of pathogens, and usage in disease prevention is increasingly popular. Previous studies showed the effectiveness of using LAB to limit harmful effects of this disease, such as the study of [ 8 ] using L. plantarum T8 and T13 bacteria and the study of [ 18 ] using heat-killed L. plantarum strain L137. Similarly, L. plantarum , L. fermentum , and P. pentosaceus supplementation of the present study demonstrated a strong resistance against V. parahaemolyticus .…”
Section: Resultsmentioning
confidence: 99%
“…L. plantarum , L. fermentum , and p. pentosaceus strains [ 8 ] that have the ability to inhibit the AHPND [ 8 ] were cultured in 100 mL of MRS broth medium (Darmstadt, Merck) supplemented with 1.5% NaCl for 48 h. Shortly after this, bacteria density was determined by OD measurement with an optical density of 1 ± 0.025, centrifuged at a rate of 7000 revolutions within 5 min, and rinsed thrice with sterile saline, and each bacteria strain was properly mixed into the commercial feed (CP brand name) containing 40% crude protein to reach a density of 10 8 CFU/g, then coated with squid oil. Feed was put in labeled plastic bags and stored at a maximum temperature of 4 °C to be used for seven days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations